The assertion of militant catholicism in the Iberian anti-Machiavellianism of the sixteenth century. De Nobilitate Christiana (1542) by Jeronimo de Osorio - Prades Vilar, Mario (2017)
This article examines the De nobilitate (1542) by Jerónimo de Osorio as a key piece for the creation and dissemination of the argumental repertoir of the sixteenth century anti-machiavellism in the Iberian culture. This imaginary focusesmainly in refuting the passage from Discourses II, 2 in which Machiavelli denies Christianity any ability to exercise military values. Contrary to this thesis, authors such as Juan Ginés de Sepúlveda, Osorio or Pedro de Ribadeneyra claim a militantand warrior Catholicism, which thrived fully in the context of the Spanish empire and its expansionist ambitions.